The Covid-19 pandemic and entrepreneurship: some reflections. Issue 5 (27th November 2020) - Liñán, Francisco; Jaén, Inmaculada
Abstract : Purpose: The Covid-19 pandemic has affected the world in an unprecedented manner. The economic recession in 2020 is expected to be the most serious since the Second World War. This study aims to analyse the likely consequences of the Covid-19 pandemic crisis on entrepreneurship and new venture activity. Design/methodology/approach: The paper focuses first on the major shocks caused by the pandemic that may affect entrepreneurial activity. To do so, the authors briefly review the literature about the previous financial crisis and its effects on entrepreneurship. Then, the manuscript means to disentangle how these shocks will impinge on the different stages and motives within the entrepreneurial process. Findings: This analysis reveals that the consequences of the pandemic for entrepreneurship will be generally damaging, but they may not be so tremendously negative as originally thought. We could initially expect a broad downturn in entrepreneurial activity. Soon after that, however, necessity entrepreneurship is likely to boom. At the same time, but to a lesser extent, high-potential entrepreneurial activity could also be fostered, provided the recovery is quick and there is sufficient support from the environment and institutions. Originality/value: This is probably one of the first academic reflections on the likely effects of the Covid-19 pandemic on entrepreneurship. It specifically addresses the role of institutions and how they may differently affect necessity and opportunity entrepreneurship. It also suggests interesting related research areas and some basic recommendations on how to help entrepreneurs overcome it.